Estimating the potential increase in consumer welfare from the introduction of 'Super Wi-Fi' service - Areum Hong; Changi Nam; Seongcheol Kim (International Telecommunications Society (ITS), 2014)
With the increasing use of smart devices recently, mobile traffic has been increasing rapidly, which in turn results in greater demand for the frequency. Many countries have attempted to use the vacant frequencies known as TV White Space (TVWS) in an effort to solve the frequency problem. Super Wi-Fi service, a wireless Internet service based on TVWS, is one of the ways TVWS is being utilized. This paper applies conjoint analysis to evaluate consumers' willingness to pay for each of the attributes of Super Wi-Fi service and estimates how much consumer welfare could be improve by the introduction of Super Wi-Fi service. The attributes of Super Wi-Fi service are coverage, a reduction in communication expenses when using mobile data, the ability to use multiple-screens, and a wide range of Wi-Fi service providers. The results based on user surveys indicated that the marginal willingness to pay (MWTP) amount per month for Super Wi-Fi service is KRW 4,717 (USD 4.6). Moreover, the MWTP amount in non-urban areas for this service is greater than that in urban areas, implying that the introduction of Super Wi-Fi service is expected to increase consumer welfare, especially in non-urban areas.
Keywords: 330